The Yellow Brick Road? Establishing a Constitutional Right to State-Funded Counsel for Matters of Civil Law in Canada - Wong, Andrea (The Journal of Public Policy, Administration, and Law, 2011)
Canadians do not have a constitutional right to state-funded counsel for matters of civil law, unlike for matters of criminal law. This article examines the reasons for this and, more importantly, the significant barriers for establishing a general constitutional right to state-funded counsel for civil cases. Analysis in this article shows that the most significant barriers for establishing such a general constitutional right have been, and will likely continue to be, the courts‘ interpretation of the Constitution from the perspective of the Charter framers and their reluctance to impose a positive constitutional obligation on government that would dictate the allocation of public funds.